PENGARUH PANDANGAN ISLAM, PELAYANAN DAN KEAMANAN TERHADAP MINAT NASABAH UNTUK MENABUNG DI BANK SYARIAH ISLAM (BSI) CABANG LAHAT (MOTIVASI, 2022)
This study aims to determine the factors that influence customers' interest in saving Bank Syariah Indonesia Branch Lahat. The independent variables used are Security, Islamic views and Services and the dependent variable used is Customer Intention in deciding to save in Bank Syariah Indonesia (BSI). This study uses primary data by distributing questionnaires to customers of Bank Syariah Indonesia (BSI). The analysis technique used in this study was a descriptive approach analyst by using Structural Equation Modeling (SEM). The results showed a positive relationship between Security, Islamic view, and Service to the customer's interest in saving. But the Islamic view variables have the positive and significant relationship.